Seamus Heaney’s Station Island: The Polyphonic Poetics of Exile - Annunciação, Viviane Carvalho da (ABEI Journal, 2013)
This article analyzes the poem “Station Island” (Station Island, 1984) by Seamus Heaney as a “polyphonic poetics of exile”. Heaney’s oeuvre is impregnated with a poetic style that combines the geographical act of frontier crossing to the linguistic work with cultural translation. This technique is most clearly observed in “Station Island” and characterizes his work as a poetic heteroglossia.Keywords: Seamus Heaney, Station Island; poetic heteroglossia.